Cover Image, Volume 70, Issue 11. Issue 11 (13th September 2022) - Gasterich, Natalie; Bohn, Amelie; Sesterhenn, Anika; Nebelo, Frederik; Fein, Lena; Kaddatz, Hannes; Nyamoya, Stella; Kant, Sebastian; Kipp, Markus; Weiskirchen, Ralf; Zendedel, Adib; Beyer, Cordian; et al.
Abstract : Cover Illustration: Lipocalin 2 is a potential regulator of inflammation in the brain and possibly involved in Multiple Sclerosis (MS) lesion formation. The picture was taken from tissue obtained from an MS patient with progressive disease course. The maximum projection identifies intracellular Lipocalin 2 (green) within an activated astrocyte (GFAP in red). (See Gasterich, N. et al, https://doi.org/10.1002/glia.24245 .)